Brainstorming Method in Islamic Education: Analysis of Learning Activities of Students at Al-Kautsar Campaka Vocational School (Universitas Pendidikan Indonesia Kampus Cibiru, 2024)
This study focuses on how to improve student learning activities in the Islamic Religious Education (PAI) learning process. This study aims to determine the effect of the brainstorming method on student learning activities in Islamic Religious Education (PAI) subjects. The research method used is descriptive quantitative. This study involved 20 tenth-grade students as samples. The results showed that 1) The brainstorming method in Islamic Religious Education (PAI) lessons at SMK Al-Kautsar Campaka has shown significant effectiveness, with a variable X value of 69.3% (good). 2) Student learning activities increased significantly after using the brainstorming method, with a variable Y value of 70% (good). 3) There was a positive and significant effect between the brainstorming method and student learning activities, with an effect of 61.5%. In the brainstorming method can be considered an effective instructional strategy to enhance student learning activities in Islamic Religious Education (PAI) subjects. Its implementation encourages active participation, idea sharing, and student engagement, thereby contributing positively to improving the overall learning process.